Surface and coordinate measurements with nanomeasuring machines - Hausotte, Tino; Balzer, Felix; Vorbringer-Dorozhovets, Nataliya; Manske, Eberhard (International Journal of Nanomanufacturing, 2012)
The nanomeasuring machine (NMM-1) was designed for surface and coordinate measurements within a measurement volume of 25 mm × 25 mm × 5 mm. The machine is equipped with three homodyne plane-mirror miniature interferometers for the measurement of the displacement of a movable corner mirror. The object being measured is placed on the corner mirror, which is positioned by a three-axis drive system. Various measurement tasks are possible depending on the probe system installed. Most of the sensors utilised are one-dimensional tactile or optical surface sensors or probes. In recent years, measurements of three-dimensional features and sidewalls are becoming more important. For these more complex measurements, probe systems with two or three directions of sensitivity are necessary and were therefore integrated into the NMM-1. The article gives an overview of the operation and properties of the NMM-1, its use for surface and coordinate measurements, of integrated probe systems and of two probing systems developed. Copyright © 2013 Inderscience Enterprises Ltd.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.lfmt.surfac
Keywords: Abbe comparator principle; Coordinate measurements; Interferometer; Machine design; Nanomeasuring; Nanometrology; Nanopositioning; Surface measurements